The Transfer of Contextual Control (Cfunc) of Multiple Derived Functions Through Equivalence Relations - de Azevedo, Sunna P.; Perez, William F.; Vichi, Christian (Perspectivas em Análise do Comportamento, 2021)
The present study investigated the transfer of contextual control (Cfunc) of multiple derived functions via equivalence relations. Four adults participated in the study. Initially, two networks comprised of equivalence relations were established: A1B1C1D1E1 e A2B2C2D2E2. Then, two functions were established for B stimuli (B1 and B2): one via positive reinforcement (key pressing) and another via negative reinforcement (button click). Those functions were also under contextual control of background colors (Blue/B1 → button click, Yellow/B1 → press Z, Blue/B2 → press Z, Yellow/B2 → button click). In a subsequent phase, the colored backgrounds originally established as functional contextual cues were related as equivalent to line patterns (Blue = Vertical; Yellow = Horizontal). The transfer of Cfunc contextual function was verified by presenting B and D stimuli on the line patterns as background (instead of the colors; Vertical/B1 → button click, Horizontal/B1 → press Z). The implications of the contextual control of multiple derived functions and of the transfer of Cfunc contextual control to a behavioral account of language and cognition are discussed.